Comparative Morphological Study on the Embryonic and Neonatal Development of the Filiform Papillae and Teeth in Mice - Soon-Jeong Jeong (치위생과학회지, 2020)
Background: In the early stages of development, teeth and lingual papillae are induced and developed through special and complex epithelial-mesenchymal interactions. Tooth completion indicates the beginning of the weaning phase, and accordingly, many oral tissues and organs are completed, and it is thought that their developmental completion times are related to each other. The purpose of this study was to clarify the embryonic and neonatal development of the filiform papillae and mandibular molar tooth, and discuss the developmental relationship between these organs by comparing the developmental completion times.Methods: Embryos at embryonic day 15 (EM15), 17 (EM17), and 21 (EM21) and mice at neonatal day 1 (NE1), 5 (NE5), 10 (NE10), and 21 (NE21) were used for experimentation. Tissues dissected from embryos and mice were fixed, and processed for histological analysis. Sections from the tissues were stained with hematoxylin and eosin for observation under a light microscope.Results: Based on the histological analysis results, the developmental process of the lingual epithelium covering the dorsal surface of the tongue was classified into three stages: initiation, morphogenesis, and functional. The development of the filiform papillae begins at EM17; undergoes rapid morphological changes in epithelial cells at EM21, PN1 and PN5, and reaches the functional stage at PN10, which is the sucking phase. Tooth development begins at EM13 or 15 and is completed at NE21 through prenatal and postnatal development.Conclusion: The development of the filiform papillae was initiated late and completed quickly through embryonic and neonatal development in comparison with the mandibular molar tooth. The filiform papillae are considered to play an important role in sucking rather than mastication as it is completed in the sucking phase.